Climate Applications - Rudd, Denis; Mills, Richard J. (Journal of Applied Business and Economics, 2020)
The climate of the organization is crucial in creating an effective organization. Climate is a part of the internal environment of the organization. Some people feel that climate results from physical layout of the company. The interior decor, the color-coordinated furnishings, the uniforms worn by the workers or the size of the offices may create a certain ambiance. Although such factors can influence workplace atmosphere, we have to define climate in a broader sense. The fabric of the organization that enables it to function and explain why it acts the way it does is called organizational culture or climate. It is defined as "the philosophies, ideologies, values, assumptions, beliefs, expectations, attitudes, and norms that knit an organization together and are shared by employees." All these behavioral concepts form an organization's consensus, implicit and explicit, on how to approach decisions and problems in the organization. In other words, climate provides a framework that explains "the ways things are done around here." There are numerous examples of organizational culture and its impact on organizations. Delta Airlines stresses teamwork among employees, Hewlett-Packard believes in entrepreneurship and PepsiCo wants aggressive managerial behavior and competition both within and outside the organization.